Sine-Cosine Weighted Circular Distributions - Shahsanaei, Fatemeh; Chinipardaz, Rahim (Statistics, Optimization & Information Computing, 2023)
This paper introduces a new family of multimodal and skew-symmetric circular distributions, namely, the sine-cosine weighted circular distribution. The fundamental properties of this family are examined in the context of a general case and three specific examples. Additionally, general solutions for estimating the parameters of any sine-cosine weighted circular distribution using maximum likelihood are provided. A likelihood-ratio test is performed to check the symmetry of the data. Lastly, two examples are presented that illustrate how the proposed model may be utilized to analyze two real-world case studies with asymmetric datasets.